2016
DOI: 10.1002/jaba.344
|View full text |Cite
|
Sign up to set email alerts
|

Teaching multiply controlled intraverbals to children and adolescents with autism spectrum disorders

Abstract: Reciprocal conversations, instructional activities, and other social interactions are replete with multiply controlled intraverbals, examples of which have been conceptualized in terms of conditional discriminations. Although the acquisition of conditional discriminations has been examined extensively in the behavior-analytic literature, little research has evaluated procedures to establish multiply controlled intraverbals. Thus, the purpose of this investigation was to evaluate the effects of procedures based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
80
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(86 citation statements)
references
References 40 publications
3
80
0
3
Order By: Relevance
“…Considering his history of explicit reinforcement for tact name responses and absence of reinforcement history for tacting the capital in the presence of the picture of the state, this result is not surprising. For some children, more intensive procedures to establish strong visual–auditory conditional discriminations may be required such as blocked trials (e.g., Ingvarsson, Kramer, Carp, Pétursdóttir, & Macias, ; Kisamore, Karsten, & Mann, ). This may be considered a limitation, or at least point of caution, for clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Considering his history of explicit reinforcement for tact name responses and absence of reinforcement history for tacting the capital in the presence of the picture of the state, this result is not surprising. For some children, more intensive procedures to establish strong visual–auditory conditional discriminations may be required such as blocked trials (e.g., Ingvarsson, Kramer, Carp, Pétursdóttir, & Macias, ; Kisamore, Karsten, & Mann, ). This may be considered a limitation, or at least point of caution, for clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the current study extend the literature on the emergence of multiply controlled intraverbal behavior in several ways. First, prior studies have demonstrated that individuals with typical and atypical development can acquire complex intraverbal responses under the control of multiple conditional and discriminative stimuli via direct training using transfer-of-stimuluscontrol procedures or prompted DORs (e.g., Braam & Poling, 1983;Kisamore et al, 2013;Kisamore et al, 2016). In addition, previous research has shown that training procedures can be arranged in ways to promote the emergence of simple intraverbal responses in individuals with typical and atypical development (e.g., DeSouza & Rehfeldt, 2013;Grannan & Rehfeldt, 2012;Miguel et al, 2005;Petursdottir & Haflidadottir, 2009), provided certain conditions are met (e.g., provided emergent responses share the response form with a different previously taught operant; Dounavi, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, because we collected data on the participant's use of DORs, but we did not specifically prompt participants to emit a DOR on each trial, the results provide some data relevant to the role of naming or the naming relation in the development of emergent stimulus relations (Horne & Lowe, 1997). In the applied literature, researchers have prompted or required DORs to overcome stimulus overselectivity in matching-to-sample tasks (Dube & McIlvane, 1999;Fisher, Kodak, & Moore, 2007;Walpole, Roscoe, & Dube, 2007), and to directly train multiply controlled intraverbals (Kisamore et al, 2016). When DORs are spontaneously emitted, they may facilitate the development of naming or the naming relation (Horne & Lowe, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A DOR procedure requires the learner to emit a response unique to each arrangement of discriminative stimuli (Green, ) before he or she has the opportunity to respond to compound arrangements of those stimuli. For example, Kisamore, Karsten, and Mann () demonstrated that requiring children and adolescents with ASD to repeat parts of a stimulus that control correct responses (e.g., “What's an animal that's red?” Say, “animal red”) led to acquisition of multiply controlled intraverbals for four of seven children. It is feasible that the introduction of a DOR requirement, such as answering self‐questions about a social situation, would function to bring conversational responses under compound stimulus control of vocal and non‐vocal mands.…”
mentioning
confidence: 99%